2022
DOI: 10.1007/s43979-022-00008-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate policy uncertainty and corporate investment: evidence from the Chinese energy industry

Abstract: In recent years, with the increasing attention paid to climate risks, the changes in climate policies are also more full of uncertainties, which have brought tremendous impact to economic entities, including companies. Using the dynamic threshold model, this study investigates the nonlinear and the asymmetric effect of climate policy uncertainty on Chinese firm investment decisions with panel data of 128 Chinese energy-related companies from 2007 to 2019. The empirical findings indicate that the influence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Governance quality contributes to better investment decisions for the corporation. However, increased EPU has adverse impacts on corporate investments [11], whereas Ren et al [12] find different impacts of EPU on corporate investments at different ranges of EPU. EPU also has negative impacts on ES and climate change mitigation by increasing CO 2 emissions [13][14][15].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Governance quality contributes to better investment decisions for the corporation. However, increased EPU has adverse impacts on corporate investments [11], whereas Ren et al [12] find different impacts of EPU on corporate investments at different ranges of EPU. EPU also has negative impacts on ES and climate change mitigation by increasing CO 2 emissions [13][14][15].…”
Section: Introductionmentioning
confidence: 94%
“…Compared to pooled regression, quantile regression offers various advantages, including being more resistant to outliers in the response measurements and making no assumptions about the distribution of the target variable [30,31]. Since EPU may have different impacts at its different ranges [12], the quantile regression could be helpful to understand the impact of EPU at its different levels.…”
mentioning
confidence: 99%
“…Hoang (2022) found a significant negative effect of CPU on R&D investment for high‐emitting firms. Ren, Shi, et al (2022) identified a nonlinear relationship between CPU and firm investment. Ye (2022) showed climate risk significantly influencing economic activity, financial markets, and energy markets.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Climate risk has also become popular in the finance literature since climate change has been found to affect financial markets (Oloko, Adediran, & Fadiya, 2022). Another dimension to the importance of climate risk is the significant impact of climate policy uncertainty on investment (Ren, Shi, & Jin, 2022; Bouri, Iqbal, & Klein, 2022). This study contributes to a growing body of research on the diversification potential of green investments.…”
Section: Literature Reviewmentioning
confidence: 99%